PROBLEMATIKA KETIDAKADILAN LINGKUNGAN DALAM PENGELOLAAN WILAYAH PESISIR DI INDONESIA - Muhamad Agil Aufa Afinnas (Mimbar Hukum, 2023)
Abstract Environmental injustice often occurs in coastal area utilization activities due to the neglect of social and environmental interests for economic interests. In this research, the problem of environmental injustice in coastal area management will be analyzed using the Taxonomy of Environmental Justice framework. Furthermore, reflection will be carried out using the Job Creation Perpu concerning environmental injustice in coastal areas. This research uses doctrinal legal research method. This research will indicate environmental injustice in the form of distributive, corrective, procedural, and social injustice. Distributive injustice is related to the unequal distribution of risks and benefits of coastal area management activities. Corrective injustice occurs because environmental law enforcement is still weak and the legal norms are also nonideal for justice awakening. Procedural injustice is related to the obstacles in accessing the right to information, the right to participation, and the right to justice. There are also social injustice related to the welfare problems of coastal communities. However, The Job Creation Perpu is considered unable to overcome the problem of environmental injustice that occurs in coastal area management so far. Abstrak Permasalahan ketidakadilan lingkungan masih sering terjadi di tengah aktivitas pemanfaatan wilayah pesisir. Ketidakadilan lingkungan dapat muncul akibat diabaikannya kepentingan sosial dan lingkungan hidup demi kepentingan ekonomi. Dalam penelitian ini, problematika ketidakadilan lingkungan dalam konteks pengelolaan wilayah pesisir akan dikaji menggunakan kerangka Taksonomi Keadilan Lingkungan. Selanjutnya, akan dilakukan refleksi terhadap Perpu Cipta Kerja dalam kaitannya dengan ketidakadilan lingkungan di wilayah pesisir. Metode penelitian yang digunakan adalah penelitian hukum doktrinal.Hasil dari penelitian ini menunjukkan bahwa ketidakadilan lingkungan, yang berupa ketidakadilan distributif, prosedural, korektif, dan sosial masih terjadi. Ketidakadilan distributif masih terjadi berkaitan dengan distribusi risiko atau dampak dan manfaat dari aktivitas pengelolaan wilayah pesisir yang timpang. Ketidakadilan prosedural yang terjadi berkaitan dengan adanya hambatan pemenuhan hak atas informasi hak akses partisipasi, dan akses keadilan. Ketidakadilan korektif terjadi akibat masih lemahnya penegakan hukum lingkungan dan norma yang ada juga belum ideal untuk mewujudkan keadilan. Yang terakhir, ketidakadilan sosial terjadi berkaitan dengan permasalahan kesejahteraan masyarakat pesisir. Akan tetapi, Perpu Cipta Kerja dinilai belum dapat mengatasi ketidakadilan lingkungan dalam pengelolaan wilayah pesisir.